Pengembangan Kawasan Wisata Danau Perintis dalam Meningkatkan Pendapatan Masyarakat Oleh Dinas Pariwisata Pemuda Dan Olahraga Kabupaten Bone Bolango - Maryam Husain; Tety Thalib; Andi Yusuf Katili (Journal of Innovative and Creativity, 2025)
Lake Perintis as a tourist attraction is a form of environmental service that provides economic value This study aims to obtain an overview of the Development of the Perintis Lake Tourism Area in Increasing Community Income by the Department of Tourism, Youth and Sports of Bone Bolango Regency. This research method uses a qualitative descriptive research type. Data collection techniques are carried out by Observation, interviews, Research and Documentation. The results of this study conclude that in terms of promotion aspects on social media that are not yet optimal, the promotion only stopped at the time of the inauguration of the 2024 Pioneer Lake tourism, this resulted in a lack of information available to tourists about the Bone Bolango Regency Pioneer Lake tourism. The condition of the facilities also still needs to be added and there are several facilities that will be repaired and need attention from the Bone Bolango Regency Government. The budget is not yet optimal, due to the limited funds allocated, causing various aspects of management, such as improving facilities and adding facilities, promoting environmental maintenance, and improving tourism services, to not run optimally. It is recommended that creative and integrated promotion be increased by utilizing social media and digital technology so that the appeal of Perintis Lake is increasingly widespread. The need to improve and add supporting facilities such as parking areas, green open spaces, and culinary and lodging facilities to improve the comfort and experience of tourists. The need to optimize the budget by increasing fund allocation, transparent financial management, and expanding cooperation with various parties, including local economic actors and local governments, to support sustainable development and increase the economic value of the Perintis Lake tourist area.